1957
DOI: 10.1002/zaac.19572880509
|View full text |Cite
|
Sign up to set email alerts
|

Schwingungsspektren geschmolzener, glasiger und kristallisierter hochpolymerer Phosphate

Abstract: RAMAN‐Spektren der Schmelzen von NaPO3 und KPO3 werden beschrieben und zugeordnet. Diesen Spektren werden Ultrarotspektren (Steinsalzbereich) von Kurrolschem Kalium‐ und Kurrolschem Natrium‐Salz (B) sowie das Spektrum des Natriumtrimetaphosphats gegenübergestellt. Für das Kurrolsche Natrium‐ und Kaliumsalz werden zwei verschiedene Kettenanordnungen mit zweier‐Periodizität diskutiert. Auch die Schmelzen der Phosphate zeigen noch eine gewisse Ordnung der Ketten. Das P3O9−−− Ion hat im Kristall die Symmetrie C3v.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1957
1957
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The removal of 6.5 water molecules of hydration of Ca 3 (P 3 O 9 ) 2 . 10H 2 O, observed in the temperature range 90-150°C destroys the crystalline network and brings to an intermediate amorphous phase 19 which does not diffract the X-ray (FIGURE 1b), nor exhibits the IR absorption bands characteristic of a cyclic phosphate P 3 O 9 3-(FIGURE 2b) 10,11,12 . The amorphous product is, according to Van Wazer 19 , probably a mixture of calcium oxide CaO and pentoxide phosphorus P 2 O 5 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The removal of 6.5 water molecules of hydration of Ca 3 (P 3 O 9 ) 2 . 10H 2 O, observed in the temperature range 90-150°C destroys the crystalline network and brings to an intermediate amorphous phase 19 which does not diffract the X-ray (FIGURE 1b), nor exhibits the IR absorption bands characteristic of a cyclic phosphate P 3 O 9 3-(FIGURE 2b) 10,11,12 . The amorphous product is, according to Van Wazer 19 , probably a mixture of calcium oxide CaO and pentoxide phosphorus P 2 O 5 .…”
mentioning
confidence: 99%
“…By the examination of the position, the profile and the intensity of this band which doesn't appear in the IR spectra of the cyclotriphosphates P 3 O 9 3-and which is located generally between 850 cm -1 and 950 cm -1 , it is then possible to distinguish between cyclotriphosphate P 3 O 9 3-and long-chain polyphosphate PO 3 -10 . Between 600 and 400 cm -1 the spectrum (c) (FIGURE 2c) shows bending vibration bands characteristic of long-chain polyphosphates 10,11 . The nature of the vibration corresponding to the different observed bands is given in TABLE 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strongly polarized band at about 685 cm −1 is assigned to the symmetric in-plane bending vibration, ν s (P-O-P), of the bridging oxygens connecting two PO 4 tetrahedra. Bues and Gehrke [54] assigned the bands in the range 250 -350 cm −1 in the spectrum of pure NaPO 3 glass to bending vibrations. On the other hand, Rouse et al [56] assigned the bands at about 212 cm −1 and 380 cm −1 to Na-O stretching and O-P-O bending vibrations, respectively.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Shih and Su [5] reviewed the work of Cotbridge and Lowe [2][3][4], and Bues and Gehrke [6], made a systematic investigation of phosphate glasses containing either alkali (Li, Na, K, Rb) or alkaline earth (Ca, St, Ba) elements in the range 2 to 200/am, and concluded that the spectra of these glasses are essentially the same except for a slight diffuseness which appears in the spectra of the alkaline earth metaphosphates. Mtiller [7] argued that P=O double bond lies in the range 1282 to 1205cm -~ in the polyphosphate chain and the P-O group is characterized by a stretching frequency at 1110cm -~ whereas the P-O-P ring frequency should occur between 805 and 740 cm -a for cyclic phosphates.…”
Section: Introductionmentioning
confidence: 99%